The Accommodation of Customary Law to Islamic Law: Distribution of Inheritance in Aceh from a Pluralism Perspectives - Ilyas, Ilyas; A.Rani, Faisal; Bahri, Syamsul; Sufyan, Sufyan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
With the emergence of receptie theory, there was a conflict between customary laws and Islamic law in the past, resulting in a protracted systemic conflict. However, the opposite occurs in the context of legal practices in Aceh, namely the accommodation of the two legal systems. This study aims to elucidate the incorporation of customary laws in Islamic law as it pertains to inheritance issues in Aceh. This study analyzes empirical legal research through the lens of legal pluralism. The data was gathered through in-depth interviews and literature reviews. This study found that various inheritance-related cases involving substitute successors, joint assets, heirs of different religions, and obligatory wills for adopted children are examples of how Islamic law accommodates customary laws. The two factors responsible for the accommodation of adat in Islamic law are the nature of the law, which is dynamic, elastic, and flexible, and the sociological condition and personality of the Acehnese, which support this integration. Moreover, this accommodation has a positive impact on the lives of people so that the maintenance and observance of adat or customs become firmer, the law functions as social control and Islamic law is cultivated in society. Theoretically, in the context of legal pluralism, accommodation between adat  in Islamic law creates a space for harmonization as the main goal of this theory, not the theory of receptie which gives birth to conflicts and  conflicts between legal systems.